2004
DOI: 10.1038/sj.ejcn.1601830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of docosahexaenoic acid-containing food administration on symptoms of attention-deficit/hyperactivity disorder — a placebo-controlled double-blind study

Abstract: Objectives: To investigate whether docosahexaenoic acid (DHA) supplementation was able to ameliorate attention-deficit/ hyperactivity disorder(AD/HD) symptoms in AD/HD children. Design and subjects: A placebo-controlled double-blind study with 40 AD/HD (including eight AD/HD-suspected) children of 6-12 y of age who were mostly without medication. Subjects of a DHA group (n ¼ 20) took active foods containing fish oil (fermented soybean milk, bread rolls and steamed bread; 3.6 g DHA/week from these foods) for 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
147
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(152 citation statements)
references
References 27 publications
3
147
1
1
Order By: Relevance
“…Similarly, adults with ADHD also show low levels of the long-chain polyunsaturated omega-3 fatty acid DHA [24]. There are conflicting reports in the literature about the cognitive benefits of omega-3 supplementation in patients with ADHD [25][26][27]. Normalizing levels of these fatty acids and reducing the AA/EPA ratio to levels observed in populations such as the Greenland Eskimos and the Japanese should be beneficial due to the association of these fatty acids with various measures of health, including CHD, which is the main cause of death in Western industrialized countries, and depression, with which ADHD is frequently comorbid [28].…”
Section: Introductionmentioning
confidence: 92%
“…Similarly, adults with ADHD also show low levels of the long-chain polyunsaturated omega-3 fatty acid DHA [24]. There are conflicting reports in the literature about the cognitive benefits of omega-3 supplementation in patients with ADHD [25][26][27]. Normalizing levels of these fatty acids and reducing the AA/EPA ratio to levels observed in populations such as the Greenland Eskimos and the Japanese should be beneficial due to the association of these fatty acids with various measures of health, including CHD, which is the main cause of death in Western industrialized countries, and depression, with which ADHD is frequently comorbid [28].…”
Section: Introductionmentioning
confidence: 92%
“…Two further studies also found improvements in aggression following supplementation compared with placebo, where aggression increased in the placebo group but remained stable in the group treated with EPA þ DHA (153,156) . Four of the studies report no differences in aggression/irritability between treatment and placebo groups following supplementation (126,155,157,158) , one study reports no differences in hostility between treatment and placebo groups (154) and one study reports no differences in anger between treatment and placebo groups (119) . One study also reports increases in aggression following supplementation with EPA þ DHA compared with placebo (156) , and one study reports decreases in aggression following placebo compared with treatment following supplementation with EPA þ DHA (154) .…”
Section: Trial Evidencementioning
confidence: 99%
“…The majority of these studies, however, measured inattention, hyperactivity, impulsivity and conduct as described by parents and teachers, but found effects only in selected measures. Three studies also found no benefits of n-3PUFA compared with placebo for inattention, hyperactivity or impulsivity (157,175) or impulsivity alone (126) , and one study found no benefits of n-3PUFA compared with current medication (Ritalin) (176) .…”
Section: Trial Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…4 Some benefits from -3/-6 supplementation were reported for children with dyslexia or ADHD, 5,6 whereas 2 studies found no benefits for ADHD with the -3 fatty acid docosahexaenoic acid alone. 7,8 No randomized, controlled trials of fatty acid treatment for either autism or DCD/dyspraxia have yet been reported, although one small open study suggested possible benefits for dyspraxic children. 9 DCD, as defined in the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV), involves specific impairments of motor function independent of general ability.…”
mentioning
confidence: 99%